Two-step continuous upgrading of sawdust pyrolysis oil to deoxygenated hydrocarbons using hydrotreating and hydrodeoxygenating catalysts - Kim, Gayoung; Seo, Jangwoo; Choi, Jae-Wook; Jae, Jungho; Ha, Jeong-Myeong; Suh, Dong Jin; Lee, Kwan-Young; Jeon, Jong-Ki; Kim, Jae-Kon (ELSEVIER SCIENCE BV, 2018)
The two-step hydrodeoxygenation of pine sawdust pyrolysis oil, or bio-oil, is performed using pairs of first-step hydrotreating and second-step hydrodeoxygenating catalysts. The reaction results demonstrate that the combination of hydrotreating carbon-supported 5 wt% Pd (5 wt% Pd/C) and hydrodeoxygenating tungstate-zirconia-supported 3 wt% Ru (3 wt% Ru/WZr) catalysts produced the highest yield of oil products and the lowest yield of cokes and tars. The hydrodeoxygenated liquid products are further analyzed using FT-IR, which indicates the removal of carbonyls and hydroxyls along with an increase of methyls. The roles of hydrotreating Pd/C are further studied using GC/MS results of the hydrotreated liquid products; these results indicate that the hydrogenation of carbonyls to alcohols and the saturation of furans occur during the first step of the hydrotreating process. The removal of carbonyls and unsaturated furans can suppress their strong adsorption to noble metal surfaces and then their carbonization to cokes.
Keywords: SUPPORTED RU CATALYSTS; BIO-OIL; MODEL-COMPOUND; GUAIACOL; BIOMASS; FUELS; BIOFUELS; STORAGE; GASES; PHASE